Importance of elevated heart rate in the very early phase of ST-segment elevation myocardial infarction: Results from the DANAMI-3 trial. Issue 4 (1st June 2019) - Nepper-Christensen, Lars; Lønborg, Jacob; Ahtarovski, Kiril A; Høfsten, Dan E; Kyhl, Kasper; Schoos, Mikkel M; Göransson, Christoffer; Laursen, Peter N; Sadjadieh, Golnaz; Ghotbi, Adam Ali; Bertelsen, Litten; Køber, Lars; et al.
Abstract: Background: Elevated heart rate is associated with poor clinical outcome in patients with acute myocardial infarction. However, in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention the importance of elevated heart rate in the very early phase remains unknown. We evaluated the impact of elevated heart rate in the very early pre-hospital phase of ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention on cardiovascular magnetic resonance markers of reperfusion success and clinical outcome. Methods: In this DANAMI-3 substudy, 1560 ST-segment elevation myocardial infarction patients in sinus rhythm without cardiogenic shock were included in the analyses of clinical outcome and 796 patients underwent cardiovascular magnetic resonance to evaluate area at risk, infarct size and left ventricular ejection fraction. Heart rate was assessed on the first electrocardiogram with ST-elevation (time of diagnosis). Results: Despite equal area at risk (33%±11 versus 36%±16, p =0.174) patients with a pre-hospital heart rate ⩾100 beats per minute developed larger infarcts (19% (interquartile range, 9–17) versus 11% (interquartile range, 10–28), p =0.001) and a lower left ventricular ejection fraction (54%±12 versus 58%±9, p =0.047). Pre-hospital heart rate ⩾100 beats per minute was independently associated with an increased risk of all-cause mortality and heart failure (hazard ratio 2.39 (95% confidence interval 1.58–3.62), p <0.001). Conclusions: Very early heart rate ⩾100 beats per minute in ST-segment elevation myocardial infarction was independently associated with larger infarct size, reduced left ventricular ejection fraction and an increased risk of all-cause mortality and heart failure, and thus serves as an easily obtainable and powerful tool to identify ST-segment elevation myocardial infarction patients at high risk.